AN ENERGY SHAPING CONTROL FOR CIRCULATING CURRENT REDUCTION OF A GRID-CONNECTED PARALLEL INTERLEAVED CONVERTER - Dr T V V Pavan Kumar, Mrs M Soujanya , Dr Amit Kumar Jain (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This paper proposes a method to regulate low frequency, parallelly interleaved, rotating currents. The inverters are paralleled with the magnetally connected inductors in this configuration. In general, the carrier interleaving is used to boost the harmonic value of the output stress. As a consequence of the two voltage source converters (VSCs) an increased circulating current (differential mode stream) flows. The reciprocal inductance of Coupled Inductors (CI) effectively reduces the high frequency components of circulating currents. However, the low frequency components can not be filtered efficiently by CI.If the circulating currents are too strong, these result in CI saturation, greater switching losses and degrade the converter's overall efficiency. This paper therefore proposes a global control strategy for a parallel grid-connected interleaved converter based on the Port Controlled Hamiltonian principle (PCH). This controller efficiently manages the active and reactive forces supplied to the grid. The controller also reduces substantially the value of the circulating low-frequency current. Converter output is simulated in relation to the regular PI control and Linear Quadratic (LQ) control.The viability of the proposed method was tested by an experimental set-up. Results obtained from the tests indicate that the efficiency of the proposed approach has been well agreed with the simulation.